The housing deficit in the city of Baghdad and the future need - Hamoudi Hassan, Hatem (International Journal of Psychosocial Rehabilitation, 2020)
The research deal with the housing deficit of its quantitative and qualitative type in the city of Baghdad due to the economic and political situation in the country. In light of the increase in population, low rats of housing construction, and the absence of housing policy in the housing sector by the state due to the abolition of the public housing corporation, The apparent increase in population and the light rat of families were the main reason for the accumulation of housing deficits in Iraqi cities especially city of Baghdad; the research aims to study and analyze the housing deficit and urban planning to provide housing and revitalize the role of the government sector in finding appropriate solutions to the problem of housing deficit by setting the necessary strategies for it. The research included the theoretical framework with three investigations, as the first topic covered the housing crisis in Iraq. The second topic also included the housing deficit in Baghdad, and the third topic covered the housing policy and the future need for housing in the city of Baghdad. The research concluded with the result, the most important of which is the lack of planning in the housing sector with the rates of population increase, and family and residential fission led to pressure on community services. As for the most important proposals, they are encouraging the ministries and government departments related to the problem of housing, such as the ministry of construction and housing and the urban planning department, to establish small cities outside the basic design of the satellite cities with manageable monthly installments with available guarantees.